Work-Sampling: A Statistical Approach to Evaluation of the Effect of Computers on Work Patterns in Healthcare - Sittig, D. F. (Methods of Information in Medicine, 1993)
An increasing number of health-care institutions are in the process of implementing clinical computing systems. The need for an accurate assessment of the clinical, administrative, social, and financial effects of such systems has been recognized. Techniques have been developed to evaluate these effects on the work patterns of health-care workers including: time-motion analysis, subjective evaluations, review of departmental statistics, personal activity records, and work-sampling. This study reviews these techniques, discusses both positive and negative aspects, and presents a step-by-step description of work-sampling.
Keywords: Work-Sampling; Work Evaluation; Nurse Charting; Time-Motion Analysis